Global Energy Assessment (GEA) - Johansson, Thomas B., 1943-; Patwardhan, Anand (Anand Prabhakar).; Nakicenovic, Nebojsa; Gomez-Echeverri, Luis.; International Institute for Applied Systems Analysis (Cambridge : Cambridge University Press, 2012)
'The Global Energy Assessment (GEA) brings together over 300 international researchers to provide an independent, scientifically based, integrated and policy-relevant analysis of current and emerging energy issues and options. It has been peer-reviewed anonymously by an additional 200 international experts. The GEA assesses the major global challenges for sustainable development and their linkages to energy; the technologies and resources available for providing energy services; future energy systems that address the major challenges; and the policies and other measures that are needed to realize transformational change toward sustainable energy futures. The GEA goes beyond existing studies on energy issues by presenting a comprehensive and integrated analysis of energy challenges, opportunities and strategies, for developing, industrialized and emerging economies. This volume is an invaluable resource for energy specialists and technologists in all sectors (academia, industry and government) as well as policymakers, development economists and practitioners in international organizations and national governments'--
Includes bibliographical references and index.
Keywords: Energy policy; Power resources; Energy development; Energy security